2011
DOI: 10.1007/s11199-011-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Science Stereotypes Mediate the Relationship between Gender and Academic Participation

Abstract: While the gender gap in mathematics and science has narrowed, men pursue these fields at a higher rate than women. In this study, 165 men and women at a university in the northeastern United States completed implicit and explicit measures of science stereotypes (association between male and science, relative to female and humanities), and gender identity (association between the concept "self" and one's own gender, relative to the concept "other" and the other gender), and reported plans to pursue science-orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
19

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 68 publications
4
84
2
19
Order By: Relevance
“…Some evidence suggests, however, that people perceive scientists to be more like men than women. Research using the Implicit Association Test (Greenwald, McGhee, & Schwartz, 1998) indicates that people implicitly associate math (Nosek, Banaji, & Greenwald, 2002;Nosek et al, 2007;Nosek & Smyth, 2011) and science (Kessels, Rau, & Hannover, 2006;Lane, Goh, & Driver-Linn, 2012;Nosek et al, 2007) with men more than with women. Moreover, research has found that liking math (Nosek et al, 2002) and the intention to pursue a STEM major or career was associated with implicit stereotypes associating men with scientists (Lane et al, 2012).…”
Section: The Association Of Men With Sciencementioning
confidence: 99%
“…Some evidence suggests, however, that people perceive scientists to be more like men than women. Research using the Implicit Association Test (Greenwald, McGhee, & Schwartz, 1998) indicates that people implicitly associate math (Nosek, Banaji, & Greenwald, 2002;Nosek et al, 2007;Nosek & Smyth, 2011) and science (Kessels, Rau, & Hannover, 2006;Lane, Goh, & Driver-Linn, 2012;Nosek et al, 2007) with men more than with women. Moreover, research has found that liking math (Nosek et al, 2002) and the intention to pursue a STEM major or career was associated with implicit stereotypes associating men with scientists (Lane et al, 2012).…”
Section: The Association Of Men With Sciencementioning
confidence: 99%
“…Gender is a complicated identity based on individuals' internal experiences of who they are. Thus, individuals can vary in the degree to which they identify with a particular gender, how important gender is to their identity, the gender roles associated with their gender, and how their gender identity influences their experience in different settings such as a classroom [1][2][3]. In addition, gender is only one of a multitude of social identities that make up who we are and how we react in certain settings.…”
Section: Introductionmentioning
confidence: 99%
“…It could also be relevant to replicate the design using indirect measures that are less sensitive to social desirability concerns (see Lane et al 2012). For instance, it is possible that the participants' would associate research aptitude more with men than with women on an implicit measure though explicitly rejecting such gender stereotypes.…”
Section: Limitationsmentioning
confidence: 99%